Perspective decorative plants for creating landscape compositions in Absheron - Мамедов, Тофик Садыг оглы; Гюльмамедова, Шалала Адил кызы (ScienceRise: Biological Science, 2016)
There are described results of scientific research works on determining works of most introduced, perspective trees, shrubs and herbaceous plants from local flora and plants from foreign countries in using of creating different compositions in Absheron. Also there are studied their biological and ecological features. It is determined that these plants are well adapted in Absheron climate conditions, very perspective and they are recommended for use in parks, gardens, in various composition creations